Influence of varieties and integrated nitrogen management on productivity and nutrient uptake in aerobic rice (Oryza sativa) - SHARMA, S K; SINGH, Y V; TYAGI, SURUCHI; TOMAR, B S (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted during the wet (kharif) seasons of 2009 and 2010 at New Delhi to study the influence of Basmati varieties and integrated nitrogen management on productivity and nutrient uptake in aerobic rice (Oryza sativa L.). The treatments included two Basmati rice varieties, viz. Pusa Basmati 1 and Pusa Basmati 1121 and eight integrated nitrogen management (INM) practices such as N control (N0); 100% recommended dose of nitrogen (RDN, i.e. 120 kg N/ha through urea); 75% RDN+25% N through farmyard manure (FYM); 75% RDN+ 25%N through green manuring (GM); 75% RDN+ 25% N through Azotobacter biofertilizers (BF); 75% RDN+25% N through vermicompost(VC); 100% N through FYM+GM+BF+VC and 100% N through FYM+GM+BF+VC+ ZnSO4. The results showed that Basmati rice variety Pusa Basmati 1 produced significantly higher grain yield as compared to Pusa Basmati 1121. Among the N management treatments, highest grain and straw yield was obtained through 100% N through FYM+GM+BF+VC+Zn followed by 100 % N through FYM+GM+BF+VC and 75% RDN+25% VC. Nutrient uptake in grain was higher in Pusa Basmati 1 over Pusa Basmati 1121. However, straw of Pusa Basmati 1121 showed higher N, Zn, Fe, Mn and Cu uptake than Pusa Basmati 1. Total N, Zn and Fe uptake in grain and straw was higher in Pusa Basmati 1 as compared to Pusa Basmati 1121. Total uptake of Mn and Cu was inclined in rice variety Pusa Basmati 1121 than Pusa Basmati 1. Application of RDN and INM showed significantly increased N, Zn, Fe, Mn and Cu uptake in grain as well as straw as compared to control.